Family Support for COVID-19 Vaccination in Older Adults: Scoping Review - Riksa Wibawa Resna; Tiara Amanda; Wahyu Nofiantoro; Mustajidah Mustajidah; Dwi Meilina Ashbahna; Rachmayanti Iskandar; Susi Susilawati (Journal of Nursing Science Update (JNSU), 2023)
Older adults are the group that has the lowest COVID-19 vaccination coverage of all age groups. Information about the safety and side effects of vaccines is a factor that causes older adults not to be vaccinated. Family as the closest support system for older adults is vital to achieving COVID-19 Vaccination. This study aimed to explore the various types of support families provide to older adults in the COVID-19 vaccination process based on published research articles. In this scoping review, the authors used four databases, Embase, Cinahl, Cochrane, Pubmed, and Google Scholar, like other reference sources, to obtain eleven articles discussing family support for the COVID-19 vaccination process. Results Based on the study using the PRISMA diagram, seven articles were eligible with the inclusion and exclusion criteria for this scoping review; from this article, it was found that the support provided by the family during the COVID-19 vaccination process in the older adults consisted of emotional, accessibility, and informational support. Providing information accompanied by solid motivation from the family is the key to the success of the COVID-19 vaccination process in older adults. Ease of accessibility is the main supporting factor beyond the motivation and information provided by the family.